Legal Protection For Bitcoin Investors In Indonesia: To Move Beyond The Current Exchange System - Tampi, Mariske Myeke (UI Scholars Hub, 2017)
Since Indonesia has known and enforced the concept of tort, an act regarded as tort is not only actions contrary to the law, but an act that violates the principles of propriety, the principles of thoroughness and cautionary principle also included in tort. Around 2010, it was found that the act of not fulfilling the decision of court which has binding power associated for compensatory money in cases of corruption becomes the basis of a tort lawsuit, where the problem is that court verdict is not a main legal source for countries which adopt civil law such as Indonesia. Therefore, this paper will explain more on regulation regarding lawsuit filing pursuant to Article 1365 Civil Code, particularly in terms of not implementing court decisions with binding power related to the fulfillment of payment of compensation in corruption